2023
DOI: 10.1001/jamanetworkopen.2023.38699
|View full text |Cite
|
Sign up to set email alerts
|

Specialty Palliative Care and Symptom Severity and Control in Adolescents and Young Adults With Cancer

Sumit Gupta,
Qing Li,
Alisha Kassam
et al.

Abstract: ImportanceAdolescents and young adults (AYAs) with cancer experience substantial symptom burden. Specialty palliative care (SPC) is recommended but often not involved or involved late.ObjectivesTo determine whether patient-reported symptom severity was associated with subsequent SPC involvement and whether SPC was associated with symptom improvement in AYAs with cancer.Design, Setting, and ParticipantsThis cohort study comprised AYAs (aged 15-29 years) with primary cancer diagnosed between January 1, 2010, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…We adhered to Statistics Canada’s recommendation not to report income quintiles in rural areas, owing to the variation of income within a single rural postal code, an approach that has been adopted by past studies. 25 28 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We adhered to Statistics Canada’s recommendation not to report income quintiles in rural areas, owing to the variation of income within a single rural postal code, an approach that has been adopted by past studies. 25 28 …”
Section: Methodsmentioning
confidence: 99%
“…We adhered to Statistics Canada's recommendation not to report income quintiles in rural areas, owing to the variation of income within a single rural postal code, an approach that has been adopted by past studies. [25][26][27][28] Using the OHIP database, we identified all primary care physician and long-term follow-up clinic visits in the year before the start date of each surveillance lookback period. We categorized Johns Hopkins' Aggregated Diagnosis Groups (ADG) scores, representing measures of morbidity, 29,30 as none, low (1-5), intermediate (6)(7)(8)(9), and high (≥ 10).…”
Section: Data Sourcesmentioning
confidence: 99%
“…This is an open access article distributed under the terms of the CC-BY License. Yet, it is always worth considering how we can improve current practice, so that fewer AYA who might benefit from palliative care miss out on receiving The findings from Gupta and colleagues 5 suggest an important role for the integration of systematic patient-reported outcome measures to prompt palliative care referrals as part of standard practice. We need research to test whether this kind of screening, linked with standardized prompts or time points for palliative care integration, enables symptoms to be addressed sooner and more effectively.…”
Section: + Related Articlementioning
confidence: 99%
“…This analysis focused on palliative care only-with interdisciplinary, psychology, or allied health interventions not captured within this data set. Using linked health service data, Gupta and colleagues 5 showed that AYA who did not have their symptoms screened with the ESAS were less likely to receive palliative care involvement of any kind. AYA whose symptom screeners showed they had worse symptoms (moderate or severe) were most likely to be referred to palliative care.…”
mentioning
confidence: 99%
See 1 more Smart Citation